The Degree of Contribution of Knowledge ‎Management to the Development of ‎Administrative Decisions in Heads of ‎Academic Departments at Jordanian ‎Universities - Al-Awamreh , Heba; Hatamleh, Habes (Jordan Journal of Educational Sciences, 2021)
This study aimed to identify the degree of knowledge management contribution to improving administrative decisions among academic department heads at Jordanian universities. The study community consisted of all academic department heads at Jordanian universities in the northern region, who numbered (216) department heads and the study sample was chosen randomly consisting of (84) department heads from public and private universities in the northern region. To achieve the goals of the study, a questionnaire was developed as a tool to identify the degree of knowledge management’s contribution to improving administrative decisions of academic department heads at Jordanian universities, where the questionnaire consisted of (22) Items after the verification of its sincerity and consistenc. The study showed the following results: The degree of knowledge management contribution to improving administrative decisions among academic department heads at Jordanian universities in the northern region was significant and there were no statistically significant differences at the level of significance (a<0.05) in the degree of knowledge management contribution to improving administrative decisions of academic department heads in Jordanian universities in the northern region according to the gender variable and the university variable. The results also showed that there were statistically significant differences at the level of significance (a≤0.05) in the degree of knowledge management contribution to the development of administrative decisions of academic department heads at Jordanian universities in the northern region according to the variable of academic rank and the differences were in favor of professor rank, while due to experience was the differences were in favor of experience category more than 10 years. In light of the study results, the researchers recommended the need to enhance opportunities for faculty members ’participation at Jordanian governmental and private universities in the decision-making process at the department level and university level as a whole